Development and quality evaluation of geriatric health mix - Thasleema Salam (Department of Community Science, College of Agriculture, 2018)
The present study entitled “Development and quality evaluation of Geriatric health mix”, was conducted in the Department of Community science, College of Agriculture, Vellayani during the period of 2016 – 2017. The objective of the study was to develop Geriatric health mixes and to evaluate their nutritional, functional, organoleptic and shelf stability. The study was intended to develop a consumer acceptable Geriatric health mix to the targeted individuals, that could supplement energy and other nutrients in the diet. Millet and cereals such as ragi, wheat rava, barley and oats were selected as base materials for the development of the health mix. The base materials were collected from the local shops. They were roasted, powdered and sieved. Ingredients such as soya flour, dehydrated vegetables, dehydrated fruit bits, skimmed milk powder and food adjunct were the other constituents in the formulation of health mix. The food adjunct added was cardamom. For standardization of the health mixes two groups of formulations were tried out for the finalization of geriatric health mix. First group included dehydrated vegetables carrots, beans and onions. Second group comprised of dehydrated fruit bits which included dried pineapple, dates and amla in honey. First group included treatments one to five and the second group included treatments six to ten. Best three treatments of each group were selected based on computed energy and NDP CAL%. Thus from first group, T1 (which comprised of wheat rava, oats, pulse, dehydrated vegetables and skimmed milk powder), T4 (which comprised of ragi, oats, soya, dehydrated vegetables and skimmed milk powder) and T5 (which comprised of ragi, barley, soya, dehydrated vegetables and skimmed milk powder) were selected as the best combinations and in second group T6 (which comprised of wheat rava, oats, soya, pulse, dehydrated fruit bits and skimmed milk powder), T9 ( which comprised of ragi, oats, soya, dehydrated fruit bits and skimmed milk powder) and T10 ( which comprised of ragi, barley, soya, dehydrated fruit bits and skimmed milk powder) were selected as the best combinations. Each treatment from the two groups were then processed into porridge and served hot to the sensory panel members. Each combination was scored based on sensory parameters for selecting the best combination. The best formulation identified from first group was T4 which comprised of ragi, oats, soya, dehydrated vegetables and skimmed milk powder (their proportions being, 40g: 20g: 20g: 15g: 5g). From the second group T10 which comprised of ragi, barley, soya, dehydrated fruit bits, skimmed milk powder was selected as the best combination (their proportions being, 40g: 20g: 20g: 15g: 5g). Assessment of consumer preference was conducted among 30 elderly people selected at random. Functional qualities of health mixes were analyzed. Yield ratio for T4 was 0.45 and for T10 it was 0.83. In the case of bulk density, T10 recorded a value of 0.66 and T4 recorded a value of 0.55. Chemical analysis of the product revealed that moisture, acidity, total ash and peroxide value for T4 were 2.60%, 0.20%, 2.82g and 1.44 meq /kg respectively. And for T10 it was 3.04%, 0.29%, 2.88g and 0.91 meq/ kg respectively. Nutrient profile of the developed health mix (T4) revealed energy, protein, carbohydrate, iron, calcium, potassium, sodium and fiber level to be 310.03kcal, 18.80g, 54.07g, 5.08mg, 272.52 mg, 172.54 mg, 5.88 mg and 7.50 % respectively. In the case of T10, it was 309.72 kcal, 17.98 g, 54.21g, 4.43 mg, 270.45 mg, 174.34 mg, 6.37 mg and 7.87% respectively. The developed health mixes were packed and kept for three months to assess shelf life at ambient conditions. The moisture, acidity and peroxide content were seen to increase with storage, but were within the prescribed limits. Microbial growth was absent during the initial, first and second month. However low bacterial count could be observed after the third month. But sensory evaluation of the products during storage period revealed acceptable results. Hence this study confirmed that health mixes with good sensory quality and shelf life could be standardized with nutritional ingredients like ragi, barley, oats and soya